Effects of nano-grooved gelatin films on neural induction of human adipose-derived stem cells. Issue 84 (21st November 2017) - Tsai, Chen-Yu; Lin, Chih-Ling; Cheng, Nai-Chen; Yu, Jiashing
Abstract : The extra cellular matrix (ECM) and cell–cell interactions facilitate the survival, self-renewing and differentiation capabilities of stem cells. Abstract : The extra cellular matrix (ECM) and cell–cell interactions facilitate the survival, self-renewing and differentiation capabilities of stem cells. Biomaterials with specific structures such as grooves, ridges, pits, or pillars can mimic the topographic landscape of the niche. Cells can "sense" the mechanical properties and surface patterns, ranging from the micro- to nano-scale, of the substrate; hence, different sizes of nano-grooves on a gelatin surface were designed. The design of grooves can be systematically modified and those structures can reflect the organization of the ECM. In previous studies, polystyrene (PS) was often used because it is easy to fabricate topographic structures. For better biocompatibility, gelatin was chosen and fabricated into ideal nano-groove films. On the other hand, gelatin can be crosslinked by using several crosslinking agents, which leads to a higher mechanical strength and better flexibility. It was known that stem cells can serve as a source of neurons in transplantation therapies. The differentiation of neurons is associated with directionality of stem cell. To investigate the effect of topographic cues on stem cells, groove pattern arrays were constructed onto gelatin surfaces. Human adipose-derived stem cells (hASCs) were seeded onto the patterned gelatin films to observe cell proliferation and differentiation.